DIGITAL TECHNOLOGIES AND SUSTAINABILITY EDUCATION IN ACCOUNTING (NAU Journal of Technology and Vocational Education, 2026)
The rapid advancement of digital technologies and the growing global emphasis on sustainability reporting are reshaping accounting education. Technologies such as artificial intelligence, big data analytics, blockchain, and cloud computing are transforming financial reporting and environmental, social, and governance (ESG) disclosure practices. However, the extent to which these technologies are integrated into sustainability-related accounting courses and their impact on students’ learning outcomes remains insufficiently explored. This study investigates the integration of digital technologies into sustainability education within accounting programs and examines their influence on students’ understanding of sustainability accounting concepts. A descriptive survey research design was adopted, involving 500 respondents comprising accounting lecturers and undergraduate accounting students. Data were analyzed using descriptive statistics and one-sample t-tests to test four research questions. The findings reveal that digital technologies are integrated at a level significantly higher than moderate (Mean = 3.88, SD = 0.60, p < 0.05). Results further indicate that digital technologies have a significant positive impact on students’ understanding of sustainability accounting concepts (Mean = 3.82, SD = 0.68, p < 0.05). However, moderate-to-high challenges persist, including inadequate infrastructure, limited faculty digital competence, and curriculum fragmentation (Mean = 3.42, SD = 0.75). Respondents strongly support strategies such as faculty training, curriculum redesign, technological investment, and industry collaboration to enhance integration (Mean = 4.12, SD = 0.58). The study concludes that while accounting education is progressively embracing digital technologies to support sustainability learning, systematic curriculum reform and institutional investment are required to ensure effective and consistent implementation. The findings contribute to the discourse on digital transformation and sustainability in accounting education and provide strategic recommendations for strengthening professional relevance in a data-driven global economy.
Keywords: Digital technologies; sustainability education; accounting education; ESG reporting; curriculum reform